Effect of salinity on nursery bi-culture of Pacific White Leg Shrimp (Litopenaeus vannamei) and Giant Prawn (Macrobrachium rosenbergii) in a biofloc system - Halim, Md. Abdul; Aziz, Dania; Arshad, Aziz; Wong, Nur Leena W. S.; Karim, Murni; Islam, Md. Ariful; Syukri, Fadhil; Rahi, Md. Lifat (John Wiley and Sons Ltd, 2025)
The current study was carried out to examine the effects of four different experimental salinities (T1 = 0‰, T2 = 5‰, T3 = 10‰, and T4 = 15‰) on growth, water quality, proximate composition, total bacterial (TB), and hemocyte counts of white leg shrimp (Litopenaeus vannamei) and giant prawn (Macrobrachium rosenbergii) in biofloc based nursery bi-culture system for 6 weeks. A total of 12 cylindrical plastic tanks (125 L) filled up 100 L water for rearing L. vannamei and M. rosenbergii post-larvae (PLs) at an equal ratio: (50 L. vannamei: 50 M. rosenbergii). At the end of the experiment, for L. vannamei, the significantly higher (p < 0.05) growth rate was recorded in T4 (15‰) compared to the other treatments. For M. rosenbergii, a significantly higher (p < 0.05) growth rate was recorded in T2 (5‰) than in other treatments. Similar to growth, the best (p < 0.05) feed conversion ratio (FCR) for -L. vannamei was found at T4 (15‰) while it was at T2 (5‰) forM. rosenbergii. Gross return, net profit, and benefit–cost ratio (BCR) analysis revealed higher profit T4 (15‰) than T3 (10‰), T2 (5‰), and T1 (0‰). TB counts were found to be significantly greater (p < 0.05) in T4 than other treatments. Hemocyte counts for L. vannamei were significantly higher (p < 0.05) in T4 (15‰) than T3 (10‰), T2 (5‰), and T1 (0‰) and for M. rosenbergii hemocyte was significantly higher (p < 0.05) in T1 (0‰) than T2 (5 ‰), T3 (10 ‰), and T4 (15‰). Therefore, it can be suggested that 15‰ salinity will be the best condition for the nursery bi-culture of white leg shrimp (L. vannamei) and giant prawn (M. rosenbergii) in the biofloc system.